Pemanfaatan Hewan Vertebrata sebagai Bahan Obat - obatan Tradisional di Kampung Kangae Desa Mekeng Detung Kecamatan Kangae - Yohanes Yan Vardus; Yuli Mira Syafriati; Fitriah Fitriah (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Indonesia is also known to have many cultural diversities, one of which is the culture of traditional medicine that has been passed down from generation to generation from ancestors. The use of animals as traditional medicine is still carried out by the people of Kangae Village. The purpose of this study is to find out how the knowledge of vertebrate animals, especially reptiles and mammals, is used as traditional medicine in Kangae Village and how the use of vertebrate animals, especially reptiles and mammals, as medicine in Kangae Village. This study uses a qualitative method. This study was conducted in Kangae Village, Mekeng Detung Village, Kangae District. Data collection techniques were carried out by observation, interviews, and documentation. The results of this study indicate that the people of Kangae Village use vertebrate animals as medicine, namely there are 5 types of animals that are used as medicine. Among the 5 types of animals, there are 3 types of reptiles and 2 types of mammals. These animals are Geckos (Teke), Monitor Lizards (Oti), Snakes (Ular), Dogs (Ahu), and Bats (Ni’i). The knowledge of the Kangae Village community regarding the use of animals as medicine is obtained in two ways, namely, traditions passed down from ancestors and finding out for themselves (through relatives, neighbors and friends) and the method of processing medicinal animals consists of roasting, chopping, and making it into a dish according to the taste of the person consuming it.